A seat at the table : Huston Smith in conversation with Native Americans on religious freedom - Smith, Huston (University of California Press, 2006)
In this collection of illuminating conversations, renowned historian of world religions Huston Smith invites ten influential American Indian spiritual and political leaders to talk about their five-hundred-year struggle for religious freedom. Their intimate, impassioned dialogues yield profound insights into one of the most striking cases of tragic irony in history: the country that prides itself on religious freedom has resolutely denied those same rights to its own indigenous people. With remarkable erudition and curiosity--and respectfully framing his questions in light of the revelation th.